'Super simple stuff?': crafting quiet in trains between Newcastle and Sydney. Issue 5 (3rd September 2017) - Hughes, Ainsley; Mee, Kathleen; Tyndall, Adam
Abstract: The demands passengers place on contemporary public transport systems are increasingly focused on providing a safe, comfortable and reliable transport experience. One expression of these demands is the recent introduction of designated quiet carriages to trains. The experience of travelling in these spaces has been given little academic scrutiny. Using a case study of the commuting experience between Newcastle and Sydney, New South Wales (NSW), Australia, this paper investigates the practices, relations and affective atmospheres of quiet carriages. The paper argues that passengers on trains come together to craft quiet through interactions between human and material actors. This crafting of quiet results in noticeably different quiet atmospheres at different times of day and in different parts of the journey. Drawing on participant observation including an auto-ethnographic account of travelling in a quiet carriage, the paper distinguishes between four types of quiet crafted by the passenger collective – sleepy and comfortable quiet, busy quiet, tense quiet and spooky quiet. These four types of quiet play upon the body with different intensities and some have stronger affects that linger after the completion of the journey.